Management of tar spot disease caused by Phyllachora grevilleae subsp. grevilleae on Hakea myrtoides (Proteaceae) - Davison, Elaine; Tay, Francis (CSIRO Publishing, 2010)
Hakea myrtoides Meisn. is an attractive shrub that has a restricted distribution in the south-west of Western Australia. It is not killed by fire but re-sprouts from basal lignotubers. Its leaves are often severely affected by tar spot disease, caused by the biotrophic, stromatic ascomycete Phyllachora grevilleae (Lév.) Sacc. subsp. grevilleae (Lév) Sacc. This disease is spread by ascospores that are produced during the wettest months of the year: late autumn, winter and spring. Badly infected populations of H. myrtoides were burnt, either in a controlled burn in November 2007, or in a wildfire in January 2008. The incidence of tar spot disease on leaves of burnt plants in 2008 and 2009 was 4.4%, while its incidence on unburnt plants was significantly higher (25.1%). The incidence of flowering in 2009 was similar in both burnt and unburnt populations. Tar spot disease is common on H. myrtoides; it is present on 77% of collections of this host in the Western Australian Herbarium (PERTH).